2020
DOI: 10.2147/ijnrd.s241422
|View full text |Cite
|
Sign up to set email alerts
|

<p>Calciphylaxis: An Analysis of Concomitant Factors, Treatment Effectiveness and Prognosis in 30 Patients</p>

Abstract: Background: Calciphylaxis is a rare but severe complication mostly affecting patients with end-stage renal disease (ESRD) and is associated with high morbidity and mortality. The natural history, concomitant factors, pathogenesis, and treatment for calciphylaxis remain equivocal. Methods: We conducted a retrospective study on patients diagnosed with calciphylaxis in a tertiary care center between January 1, 2012, and December 31, 2017. We describe demographics, co-morbidities, laboratory parameters, effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Skin disorders associated with HD can markedly affect patients’ quality of life and can negatively impact their mental and physical health [ 21 ]. CUA is triggered by an imbalance in the promoters and inhibitors of vascular calcification caused by the inflammatory changes that occur in uremia [ 22 ]. STS has been shown to improve skin lesions caused by calciphylaxis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin disorders associated with HD can markedly affect patients’ quality of life and can negatively impact their mental and physical health [ 21 ]. CUA is triggered by an imbalance in the promoters and inhibitors of vascular calcification caused by the inflammatory changes that occur in uremia [ 22 ]. STS has been shown to improve skin lesions caused by calciphylaxis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a very serious and frequently fatal condition of cutaneous microvascular calcification and thought to be an independent risk factor linked to all-cause mortality [ 2 , 3 ]. Although rare, it is most commonly documented in patients with chronic kidney disease (CKD), in particular those with end-stage renal disease (ESRD), affecting up to 1–4% of ESRD patients, associated with high morbidity and mortality [ 4 , 5 , 6 ] Once diagnosed, prognosis is often poor, even with treatment, with an associated mortality of around 45–80% at one year [ 2 , 7 ]. CKD patients are at increased risk for developing vascular calcification due to their associated uraemia which predisposes to inflammation and endothelial dysfunction, although it has rarely been reported in patients without evidence of renal dysfunction, termed non-uraemic CUA [ 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact pathogenesis of CUA is undetermined, it is thought to result from extensive microvascular calcification and thrombosis within the media of arterioles, occlusion of which can result in necrosis of the overlying skin and soft tissues [ 5 , 6 , 8 ]. The precise pathophysiology of microvascular calcification is unclear; it is suggested that there is likely an underlying imbalance between promoters and inhibitors of vascular calcification in those who develop this condition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations